PEMBELAJARAN KOLABORATIF BERBASIS PROYEK PADA PEMBUATAN MURAL DI TB-TK SANTA URSULA BANDUNG - Aryani, Dewi Isma; Pandanwangi, Ariesa; Wangsaputra, Priscylia Susanto; Baene, Basituasi (Servirisma, 2024)
Maranatha Christian University is a private university in Bandung which claims to be a research- based teaching university by upholding the ICE values, namely integrity, care, excellence in its tridharma program. One of them is in the form of community service activities through the art medium of wall painting (murals) involving lecturers from the Bachelor of Visual Communication Design Program and the Bachelor of Fine Arts Program, Faculty of Fine Arts and Design as material formulators and facilitators. The activity entitled "Community Service through Making Flora and Fauna Themed Murals at TB-TK Santa Ursula Bandung" was carried out using the Asset Based Community Development (ABCD) method for project-based collaborative learning for the students involved in two implementation sessions. This activity targets partners, namely the basic education institution TB-TK Santa Ursula Bandung. This community service activity succeeded in providing technical insight and creativity in terms of illustration design in several public space locations at TB-TK Santa Ursula Bandung. These outcomes are demonstrated in several wall paintings, or murals, that the Maranatha Christian University faculty and student service team did.